Mechanism, contributing factors, and coping strategies of alarm fatigue in intensive care nursing: a qualitative study - Zhu, Ling; Wei, Siying; An, Yawen; Hu, Wenjun; Xie, Xiaofeng (Frontiers in Public Health, 2025)
ObjectiveTo explore the mechanism, contributing factors of alarm fatigue among nurses in Intensive Care Units (ICUs), and to develop targeted coping strategies.MethodsA combination of purposive and snowball sampling was employed to recruit 27 frontline clinical nurses from various ICU departments. Semi-structured interviews were conducted, and an inductive content analysis of the interview transcripts was performed based on Cognitive Load Theory and the Job Demands-Resources Model.ResultsThe study found that alarm fatigue involves dynamic shifts among three cognitive states—cognitive reserve deficit, cognitive load balance, and cognitive overload—with overload being the immediate trigger. Nurses often enter ICU work with limited cognitive reserves. Whether they maintain balance or enter overload depends on the intensity of alarm-related demands and the availability of supportive resources. High-intensity demands for alarm response, such as high alarm frequency, persistent false alarms, multitasking, night shifts, and work–family conflict, are risk factors for alarm fatigue. Resources for alarm response may function as either effective or inadequate support, aligning with protective or risk factors, respectively. Effective support helps alleviate cognitive load and includes effective team collaboration, management’s emphasis on alarm management, comprehensive theoretical training, high psychological adaptability, a strong sense of responsibility, and extensive work experience. Conversely, inadequate support increases cognitive load and includes lack of practical training, absence of formal regulations, outdated and malfunctioning equipment, crowded and noisy layout, emotional personality traits, insufficient or poor sleep, and suboptimal health status.ConclusionCognitive load as a mechanism linking the interaction between alarm response demands and available resources in the development of alarm fatigue among ICU nurses. To mitigate alarm fatigue, it is essential to reduce the intensity of alarm demands while enhancing resource support to relieve cognitive load. Organizational efforts should optimize alarm systems, establish formal protocols, and provide comprehensive training. Teams should reinforce collaboration and mutual support. Individually, nurses are encouraged to enhance psychological self-regulation and maintain sufficient sleep and physical health.